An unusual "mass" within the left atrium: Localized aneurysm of a patent foramen ovale tunnel. Issue 5 (25th March 2018) - Güvenç, Tolga S.; Güzelburç, Özge; Asarcikli, Lale Dinç; Can, Fatma; Çetin Güvenç, Rengin; Eren, Mehmet
Abstract : Masses on the interatrial septum are usually caused by myxomas or thrombi within a patent foramen ovale. We report a 53‐year‐old male patient with a hollow mass within the left atrium that was incidentally found during a routine transthoracic echocardiography. Further investigation of the mass with transesophageal two‐ and three‐dimensional echocardiography has revealed that the mass was a localized aneurysm of a patent foramen ovale tunnel. While aneurysms of interatrial septum are relatively common in normal population, to the best of our knowledge, present case is the first report of a localized aneursym of a patent foramen ovale tunnel.